SCIENTIFIC ARTICLE WRITING ASSISTANCE AND PUBLICATION OF COMMUNITY SERVICE RESULTS: DISSEMINATION STAGE AND ACADEMIC REPUTATION - Nuryati Nuryati; Sakti Andayani; Nurhasanah Nurhasanah; Mutoharoh Mutoharoh; Phillip G. Queroda (Yayasan Education and Social Center, 2026)
Community Service (PkM) activities frequently produce practical innovations and community empowerment outcomes; however, many results remain undocumented in scientific publications. Limited understanding of academic writing structures, publication procedures, and journal selection contributes to the low dissemination of PkM outputs. This community engagement program aimed to enhance participants' competencies in scientific article preparation and publication strategies to support broader dissemination and academic reputation development. The program employed a participatory training and mentoring approach involving workshops, guided writing sessions, manuscript reviews, and publication consultations. Activities were conducted through stages including needs assessment, training implementation, article development assistance, and evaluation. Participants consisted of lecturers and community service practitioners involved in institutional PkM programs. Results demonstrated increased participant understanding regarding article structure, journal standards, referencing techniques, and publication processes. Participants showed significant improvement in transforming PkM reports into publishable manuscripts. The mentoring process also enhanced participants' confidence and readiness to submit manuscripts to accredited journals. This initiative contributed not only to improved scholarly productivity but also to strengthening institutional academic visibility and dissemination practices.